2011
DOI: 10.1242/dev.059022
|View full text |Cite
|
Sign up to set email alerts
|

The APC/C activator FZR1 coordinates the timing of meiotic resumption during prophase I arrest in mammalian oocytes

Abstract: FZR1, an activator of the anaphase-promoting complex/cyclosome (APC/C), is recognized for its roles in the mitotic cell cycle. To examine its meiotic function in females we generated an oocyte-specific knockout of the Fzr1 gene (Fzr1Δ/Δ). The total number of fully grown oocytes enclosed in cumulus complexes was 35-40% lower in oocytes from Fzr1Δ/Δ mice and there was a commensurate rise in denuded, meiotically advanced and/or fragmented oocytes. The ability of Fzr1Δ/Δ oocytes to remain prophase I/germinal vesic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(71 citation statements)
references
References 75 publications
3
68
0
Order By: Relevance
“…Reduction of activity of ETC-1 and APC/C also caused the premature NEBD phenotype with low-penetrance during prophase I. In mammalian oocytes, APC/C activity is required to maintain low cyclin B1 levels during prophase I arrest (Reis et al, 2007;Holt et al, 2011). CYB-1-dependent phosphorylation of the nuclear pore component NPP-12 (Gp210) is required for timely NEBD during mitosis (Galy et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Reduction of activity of ETC-1 and APC/C also caused the premature NEBD phenotype with low-penetrance during prophase I. In mammalian oocytes, APC/C activity is required to maintain low cyclin B1 levels during prophase I arrest (Reis et al, 2007;Holt et al, 2011). CYB-1-dependent phosphorylation of the nuclear pore component NPP-12 (Gp210) is required for timely NEBD during mitosis (Galy et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Significantly, even within the inhibitory cAMP-rich follicular environment within the ovary, Fzr1 D/D oocytes exhibited an increased tendency to undergo GVBD that was related to elevated cyclin B1 levels. Importantly, in Fzr1 D/D oocytes, there was no change in the levels of Cdc25B, a potential APC/C Cdh1 substrate (Holt et al 2011), altogether underlining the importance of the APC/ C-cyclin B1 pathway for regulating G2/prophase arrest independent of Cdk1 phosphorylation status. Interestingly, even though many aspects of follicular physiology remained intact in Fzr1 D/D mutant mice, there was nevertheless a 35-40% reduction in the numbers of cumulus-enclosed oocytes (Holt et al 2011), suggesting that defects in oocyte-centred control brought about through APC/C de-regulation were detrimental to overall follicular health and integrity.…”
Section: Cdh1mentioning
confidence: 93%
“…It was found that such Cdh1-depleted oocytes exhibited an increased susceptibility to undergoing GVBD even under conditions in which cAMP levels were chemically sustained using the phosphodiesterase inhibitor, milrinone. More recently, this mechanism has R62 H Homer been shown to be physiologically relevant for sustaining the reservoir of G2/prophase-arrested oocytes using an in vivo mouse model in which Fzr1 was specifically deleted from growing and mature oocytes using Cre-LoxP technology (Fzr1 D/D mice; Holt et al 2011). Significantly, even within the inhibitory cAMP-rich follicular environment within the ovary, Fzr1 D/D oocytes exhibited an increased tendency to undergo GVBD that was related to elevated cyclin B1 levels.…”
Section: Cdh1mentioning
confidence: 99%
“…Oocytes were handled in M2 media containing 2.5 µM milrinone (Sigma-Aldrich) under mineral oil at 37 °C, and maturation was stimulated by milrinone washout, timed relative to extrusion of the first polar body. 70 Microinjections were performed on the heated stage of a Nikon TE300 inverted microscope as previously described.…”
Section: Methodsmentioning
confidence: 99%